2012
DOI: 10.1098/rstb.2012.0013
|View full text |Cite
|
Sign up to set email alerts
|

Why nature chose phosphate to modify proteins

Abstract: The advantageous chemical properties of the phosphate ester linkage were exploited early in evolution to generate the phosphate diester linkages that join neighbouring bases in RNA and DNA (Westheimer 1987 Science 235, 1173 -1178. Following the fixation of the genetic code, another use for phosphate ester modification was found, namely reversible phosphorylation of the three hydroxyamino acids, serine, threonine and tyrosine, in proteins. During the course of evolution, phosphorylation emerged as one of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
291
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(296 citation statements)
references
References 10 publications
3
291
0
2
Order By: Relevance
“…Furthermore, being negatively charged at physiological pH provides phosphate with signalling properties, including the attachment of a phosphate group to a specific amino acid, thereby altering the overall charge of the protein and affecting its functions [2]. In fulfilling these varied roles, phosphate moieties circulate between organic molecules, generally being passed along via phosphotransfer reactions involving nucleotide triphosphates.…”
Section: Importance Of Studying Phosphate Homeostasismentioning
confidence: 99%
“…Furthermore, being negatively charged at physiological pH provides phosphate with signalling properties, including the attachment of a phosphate group to a specific amino acid, thereby altering the overall charge of the protein and affecting its functions [2]. In fulfilling these varied roles, phosphate moieties circulate between organic molecules, generally being passed along via phosphotransfer reactions involving nucleotide triphosphates.…”
Section: Importance Of Studying Phosphate Homeostasismentioning
confidence: 99%
“…70 Hultquist's phosphoryl transfer experiments can be used as a plausible explanation for the accumulation of τ-pHis with the decrease in π-and bis-pHis over time (Scheme 3). Phosphoryl transfer reactions (1)(2)(3)(4)(5)(6)(7)(8) suggest that the phosphoryl group of pHis can be donated to the imidazole nitrogen of His or α-N-acetyl-His. Comparison of (1) and (5), with (7) and (8) suggests that π-pHis has the more labile phosphorus nitrogen (P-N) bond compared with τ-pHis.…”
Section: Chemistry Of Phosphohistidinementioning
confidence: 99%
“…Hence, it should be of no surprise that phosphorylation affects protein conformation, protein-protein interactions, biochemical pathways and its dysregulation is connected to many disease states. 2 There are nine known phosphorylated amino-acid residues Ser, Thr, Tyr, histidine (His), lysine (Lys), arginine (Arg), aspartic acid (Asp), glutamic acid (Glu) and cysteine (Cys). 2 The hydroxy O-linked phospho-residues, phosphoserine (pSer), phosphothreonine (pThr) and phosphotyrosine (pTyr) have been extensively studied, most probably due to their relative stability in acidic conditions routinely used for analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A common approach is to generate phospho-mimicking (aspartic or glutamic acid) amino acid substitutions of the site of interest and to determine if the observed phenotypes are reversed or neutralized. However, since the chemical environment introduced by phosphorylation is not completely equivalent to that of negatively charged residues, the failure rate of such studies is high, and the behavior of phosphomimetic mutations can be hard to interpret (Hunter 2012;Dephoure et al 2013). In our studies, none of the phospho-mutants showed growth defects under normal conditions (in contrast to the full ORF deletion mutants, which exhibited mild-tosignificant growth defects) (Figure 2A), suggesting that the engineered phosphosite substitutions behave similarly to wild type.…”
Section: Discussionmentioning
confidence: 99%